The Impact of CRD IV on Bank Lending - Matias Huhtilainen (European Journal of Government and Economics (EJGE), 2019)
This study addresses the post-financial crisis EU banking regulation reform CRD IV. The specific focus is on the relationship between increased capital requirements and the subsequent change in both supply and the price of bank credit. This study employs a twofold data consisting of a panel of Finnish unlisted savings and cooperative banks' key figures over the period 2002-2018 and a representative survey conducted with personnel of Finnish institutions. In addition to the consistent finding in regards to the effect of bank profitability as well as fairly consistent findings in regards to the effect of bank size and GDP growth, the key finding suggests a slight decrease in loan supply under the CRD IV.
Keywords: G28; G21; K22; 330; Basel III; CRD IV; lending; capital requirements